Transformational Leadership, Self-Efficacy, and Employee Performance: The Mediating Role of Innovative Work Behavior and the Moderating Effect of Islamic Work Ethics - Rendra Adi Dharma; Arik Susbiyani; Mohammad Thamrin; Nurul Qomariah; Mutiara Sari Dewi (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
Employee performance remains a key determinant of organizational effectiveness, particularly in public sector institutions that are expected to deliver high-quality public services while maintaining ethical standards. Although previous studies have extensively examined the effects of transformational leadership and self-efficacy on employee performance, limited empirical evidence explains how innovative work behavior mediates these relationships and how Islamic work ethics strengthen their effectiveness. This study investigates the direct effects of transformational leadership and self-efficacy on employee performance, examines the mediating role of innovative work behavior, and evaluates the moderating effect of Islamic work ethics. A quantitative explanatory research design was employed using a census approach involving 98 employees of the Regional Development Planning Agency (BAPPEDA) of Jember Regency, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0. The findings indicate that transformational leadership and self-efficacy significantly enhance innovative work behavior and employee performance. Innovative work behavior partially mediates the relationships between transformational leadership, self-efficacy, and employee performance. Furthermore, Islamic work ethics strengthen the positive influence of transformational leadership and innovative work behavior on employee performance, highlighting the importance of ethical values in improving organizational outcomes. This study extends the organizational behavior literature by integrating leadership, psychological capability, innovation behavior, and Islamic work ethics into a comprehensive framework for enhancing employee performance in public sector organizations.